Teachers’ role model behavior and the quality of the student–teacher relationship as prerequisites for students’ attitudes toward peers with learning difficulties - Löper, Marwin Felix; Hellmich, Frank (Frontiers in Education, 2024)
The introduction of inclusive education in primary schools has raised many questions about the impact of teachers' role model behavior on the social participation of students with learning difficulties. Based on the "theory of social referencing", this study examines whether students' attitudes towards peers with learning difficulties are predicted by perceptions of their teachers' role model behavior and the quality of the student-teacher relationship in the classroom. A questionnaire was completed by N = 753 primary school students regarding their perceptions of the student-teacher relationship, their attitudes towards peers with learning difficulties, and their perceptions of teacher behavior towards students with learning difficulties. The results of a structural equation model indicate that students' attitudes towards peers with learning difficulties can be explained significantly by their perceptions of teacher behavior and their perceptions of the quality of the student-teacher relationship in the classroom. The effect of students' perceptions of teacher behavior on their attitudes towards peers with learning difficulties is mediated by their perceptions of the studentteacher relationship. Thus, students focus more on teacher behavior when they perceive a positive student-teacher relationship. Our findings emphasize the importance of teachers' role model behavior in inclusive classrooms and offer opportunities to enhance the social participation of students with learning difficulties in inclusive primary school education.